1981
DOI: 10.1111/j.1476-5381.1981.tb10994.x
|View full text |Cite
|
Sign up to set email alerts
|

THE BINDING OF [3H]‐PROSTACYCLIN TO MEMBRANES OF A NEURONAL SOMATIC HYBRID

Abstract: [3H]‐prostacylin bound to a washed membrane preparation of the NCB‐20 neuronal hybrid cell line. Kinetic analysis of [3H]‐prostacyclin binding suggested a simple, non‐cooperative bimolecular interaction between the ligand and a single receptor population. The equilibrium dissociation constant was 16.6 nm, and binding at a saturating [3H]‐prostacyclin concentration enabled the receptor density of 2.57 × 105 receptor molecules per cell to be calculated. At 20°C the rate constant for the forward reaction (k+1) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…These variations may be due to the short half life of this prostaglandin. Blair & McDermot (1981), Corsini et al (1987) and Adie et al (1992) have shown that PGE 1 , a more stable endogenous prostanoid, is a potent agonist for the IP-receptor in both binding and physiological studies. The eective relaxations of the human bronchi observed with PGE 1 (present report) suggest that, this prostaglandin, may be the preferential natural activator for IP-receptor in human airways in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…These variations may be due to the short half life of this prostaglandin. Blair & McDermot (1981), Corsini et al (1987) and Adie et al (1992) have shown that PGE 1 , a more stable endogenous prostanoid, is a potent agonist for the IP-receptor in both binding and physiological studies. The eective relaxations of the human bronchi observed with PGE 1 (present report) suggest that, this prostaglandin, may be the preferential natural activator for IP-receptor in human airways in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…PGI2 receptor sites have been identified in several tissues, including platelets [1,2], vascular smooth muscle [3] and the NCB-20 cell line [4]. Both the platelet and vascular effects of PGI2 appear to be mediated, via a G-protein, by the adenylate cyclase enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Bound and free radioligand were separated by rapid centrifugation after incubation for 4 min at room temperature. NCB-20 cells NCB-20 cells were cultured and homogenates and membrane suspensions prepared as described previously (Blair & MacDermot, 1981 Isolated smooth muscle preparations Spiral strips of rabbit aorta, dog saphenous vein and guinea-pig trachea were set up in conventional organ baths (8 ml) for isometric tension recording as described previously (Jones et al, 1982 In human PRP, AH 6809 counteracts PGD2-induced inhibition of aggregation whereas the action of PGI2 is slightly enhanced (Keery & Lumley, 1985 Figure 4). These concentrations are at least 300 fold higher than those used in the aggregation experiments and this provides additional evidence that thromboxane receptor block does not make a significnt contribution to the inhibitory action of EP 035 and EP 157.…”
Section: Introductionmentioning
confidence: 99%